Simulation of the exclusion principle in the neutron-16O interaction through a repulsive term and application to a three-body calculation of the O16(d,p)17O reaction - Bund, G. W. [UNESP]; Ueta, K. (American Physical Society (APS), 1995)
A two-term s-wave separable potential which generates only the 2s1/2 single-particle state in O17 and reproduces the low energy phase shift is constructed. The two-term potential, together with a d-wave separable potential which reproduces the 1d5/2 single-particle state in O17, is used in a three-body Faddeev calculation of the O16(d,p)17O reaction. © 1995 The American Physical Society.